Learning Methods for Children with Dyslexia - Istiqamah Hafid (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Background: Reading is an ability that every human being must possess. We will always encounter writings that require reading and comprehension skills. Still, dyslexic children have difficulty in Reading, which causes dyslexic children to experience a decline in academics and can potentially experience unpleasant behavioral problems from their environment, where children can be ignored by their friends, even to the point of becoming victims of bullying so that several methods need to be applied to help them. This study aimed to determine the various methods that can be applied to help dyslexic children. The research method used is a literature study that presents a complete survey by summarizing, describing, and combining relevant research, packaged using a narrative review. Four methods can be identified based on the journals collected: the Orton-Gilingham method, Treatment of spelling, Reading and writing skills, Learning to read without spelling (BMTM), and the Reading aloud method. The results of this study are expected to help teachers provide learning methods to dyslexic children.